2016
DOI: 10.1080/23288604.2016.1220776
|View full text |Cite
|
Sign up to set email alerts
|

Global Health Partnerships for Continuing Medical Education: Lessons from Successful Partnerships

Abstract: The past decade has witnessed an increase in global partnerships created to strengthen health systems and provide training to health professionals in low-and middle-income countries. These partnerships are complex interventions. This study focused on unpacking the characteristics of global partnerships that provide continuing education for health professionals. A realist approach underpinned the research design to identify the mechanisms that shape successful global partnerships. Two case studies focusing on g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Authorship lists were interdisciplinary in thirteen articles [ 29 , 34 , 35 , 37 , 39 , 42 49 ] and included Southern partners in sixteen articles [ 29 , 34 37 , 39 , 41 44 , 46 51 ]. Where all authors’ primary geographic affiliations could be identified ( n = 29 articles, 152 authors), 120 (79%) authors were affiliated with institutions located in the global North - Canada [ 32 , 35 , 37 , 39 , 41 , 44 , 48 , 52 ]; Europe (Switzerland, Ireland, the United Kingdom, Germany, the Netherlands) [ 30 , 31 , 38 , 40 , 45 , 50 , 53 , 54 ]; the United States [ 29 , 33 , 34 , 36 , 49 , 55 – 58 ]; Australia [ 51 ] - and 32 (21%) were located in the global South (Kenya [ 46 ], Nepal [ 47 ], Rwanda [ 43 ], and Uganda [ 42 ]).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Authorship lists were interdisciplinary in thirteen articles [ 29 , 34 , 35 , 37 , 39 , 42 49 ] and included Southern partners in sixteen articles [ 29 , 34 37 , 39 , 41 44 , 46 51 ]. Where all authors’ primary geographic affiliations could be identified ( n = 29 articles, 152 authors), 120 (79%) authors were affiliated with institutions located in the global North - Canada [ 32 , 35 , 37 , 39 , 41 , 44 , 48 , 52 ]; Europe (Switzerland, Ireland, the United Kingdom, Germany, the Netherlands) [ 30 , 31 , 38 , 40 , 45 , 50 , 53 , 54 ]; the United States [ 29 , 33 , 34 , 36 , 49 , 55 – 58 ]; Australia [ 51 ] - and 32 (21%) were located in the global South (Kenya [ 46 ], Nepal [ 47 ], Rwanda [ 43 ], and Uganda [ 42 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Common among all thirty articles was at least some attention to the interpersonal experience of being involved in GHPs. Many described relational concepts such as mutual trust [ 28 , 36 , 37 , 42 , 45 , 47 , 56 , 57 ], respect, and understanding [ 28 , 36 , 47 , 55 ] as central to their findings. Some authors directly described the value of building personal relationships and friendships in GHPs [ 28 , 30 , 39 , 41 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Authorship of articles was of interest to us as a marker of who is granted authority or responsibility for reporting on a GHP. Authorship lists were interdisciplinary in thirteen articles (29,34,35,37,39,(42)(43)(44)(45)(46)(47)(48)(49) How did authors portray the contexts in which their GHPs were situated?…”
Section: Resultsmentioning
confidence: 99%
“…Many described relational concepts such as mutual trust(28,36,37,42,45,47,56,57), respect, and understanding (28,36,47,55) as central to their ndings. Some Similarly, many authors described the establishment of shared values, goals, mission, and vision early in the partnership as foundational(31,33,36,39,46,48,55,57).…”
mentioning
confidence: 99%